Pengenalan Konsep Dasar Rantai Pasok Menggunakan Supply Chain Board Game - Adelino, Muhammad Ilham; Chairi, Maiyozzi; Imani, Rafki (ANDIL Mulawarman Journal of Community Engagement, 2024)
Supply chain is a coordination within a unit of activity related to the transfer of products and services from suppliers to consumers. It is necessary to have transparency of information between these lines to balance upstream and downstream chain lines. Limited information will cause distortion of information which causes a bullwhip effect in the supply chain. The implementation of this Community Service was carried out at the Semen Padang Vocational School. The supply chain game is a learning medium that we provide to the students of the vocational school. The games can be a good basic provision before these students go into the field later. In its implementation, the group that acts as a distributor becomes the sole winner with a total cost of SCG3500.